The power of choice: How institutional selection influences restoration success in Africa. (May 2021) - Walters, G.; Baruah, M.; Karambiri, M.; Osei-Wusu Adjei, P.; Samb, C.; Barrow, E.
Highlights: Restoration projects often have both biological and social outcomes. How the intervention is planned or implemented can help or hinder restoration implementation. Those planning restoration projects have power to influence them through the choices that they make. Institutional choice, the partners with which agencies choose to work, and so recognise, can be a factor influencing restoration success. Despite positive ecological outcomes, social outcomes may not be achieved, hindering future participation or support for restoration. Abstract: Restoration of degraded ecosystem functions and services is an important component of conservation and sustainable development because it allows people to improve human livelihoods by reviving important ecosystem services. For restoration to be achieved a variety of factors must be in place such as policies, laws, capacity and spaces in which to debate restoration decisions, amongst others. Restoration work is typically supported by restoration projects, requiring participants to decide to restore an ecosystem and so participate in restoration action. How the intervention is planned or implemented can help or hinder that restoration process. Those planning restoration projects, intervening agents, have power to influence projects through the choices that they make. For one choice, institutional choice, the local partners with which outside agencies choose to work, and thus recognise, can be another factor influencing restoration success. Poor institutional choices can have negative impacts on conservation interventions. This paper uses five case studies from Africa (Burkina Faso, two from Ghana, Senegal and Tanzania) to understand how restoration interventions are impacted by the choice and recognition dynamics of intervening agents. While in all five cases, some restoration was achieved, in four of the case, there were negative consequences for social outcomes. In the fifth case, the project was implemented with respect for local knowledge and in ways that local stakeholders intended. The paper ends by proposing ways that intervening agents can improve their actions and so enable restoration projects achieve their objectives, specifically by presenting guidance for making institutional choices to help ensure restoration implementation.